RELATIONSHIP BETWEEN LEUKOCYTE COUNT AND PROTEINURIA IN COVID-19 PATIENTS - Anggar Setiorini; Indranila Kustarini Samsuria; Dwi Retnoningrum; Ariosta Ariosta (Jurnal Kedokteran Diponegoro, 2023)
Background: Coronavirus Disease 2019 (COVID-19) is a disease caused by SARS-CoV-2 with flu-like symptoms that could be serious in high-risk individuals. The use of laboratory parameters is determined as a predictor in improving the quality of care and thereby reducing mortality and morbidity. One of the laboratory parameters itself is hematological examination, including leukocyte count. Several studies had shown that an increase in WBC count was independently associated with an increased risk of proteinuria.